Proposta de framework baseado na capacidade absortiva para transformação ágil com foco na superação de barreiras em departamentos de tecnologia da informação - Fernandes, Nadia Pedrosa (2021)
A traditional approach to project management or product development created in the 1970s began to prove outdated, with its first stages of planning and providing the requirements, with the necessary changes and aggressive in most markets. The agile approach thus emerges as a promise to improve companies' responsiveness and innovation and leverage the performance of their technology projects, which leads companies into an agile race in the early 2000s - a phenomenon known as agile transformation. After a few years of agile practices, the literature has scientifically proven its benefits, but it does not provide guidance on how to carry out an agile transformation and even less on how to face barriers that are so characteristic of this process. In this context, the main objective of this research was to propose a framework that presents actions to overcome barriers of agile transformation, from the perspective of absorptive resources (ACAP), in Information Technology (IT) departments. To this end, the theme of agile transformation was explored through in-depth research with agile transformation participants. The identified transcripts were analyzed using the Grounded Theory strategy in three iterative analysis cycles: open, axial and selective. Data analysis procedures were based on the technique of constant comparisons that support the analysis cycles of Grounded Theory with the support of the Atlas.ti tool. Data were collected and propagated until the results of the identifications were incorporated and triangulated with the support of documental research to result in the elaboration of the framework with actions to overcome barriers of agile transformation. Evidence of the use of ACAP was found to a greater or lesser degree in the overcoming of barriers in all the declared ones, however, the greatest focus of actions resides on potential ACAP, to the detriment of the ACAP performed. As a theoretical contribution, the research required the addition of two new dimensions: propagation and adaptation and a more iterative and recursive ACAP flow with knowledge propagation as an elementary condition for agile transformation success. Based on the literature review and the findings of this research, some prescriptions were developed for the practitioner community to facilitate agile transformation.